3D-Array Token Petri Nets Generating Tetrahedral Picture Languages - Kalyani, T.; Sasikala, K.; Thomas, D. G.; Robinson, Thamburaj; Nagar, Atulya K.; Paramasivan, Meenakshi (Combinatorial Image Analysis, 2020)
The study of two-dimensional picture languages has a wide application in image analysis and pattern recognition [5, 7, 13, 17]. There are various models such as grammars, automata, P systems and Petri Nets to generate different picture languages available in the literature [1–4, 6, 8, 10–12, 14, 15, 18]. In this paper we consider Petri Nets generating tetrahedral picture languages. The patterns generated are interesting, new and are applicable in floor design, wall design and tiling. We compare the generative power of these Petri Nets with that of other recent models [9, 16] developed by our group.